Catastrophe : risk and response - Posner, Richard A. (Oxford University Press, 2004)
Posner considers how we can better prepare for the chance of an event - such as voraciously self-replicating nanomachines, a world-ending accident in a high-energy partical accelerator or an asteroid collision - so catastrophic that we find it hard to conceive of the consequences.